Gradient Descent Method for Perron Eigenvalue Minimization of Incomplete Pairwise Comparison Matrices - Hailemariam Abebe Tekile (International Journal of Mathematics And its Applications, 2019)
Pairwise comparison matrices are often employed as a basic tool in multi-criteria decision-making. Incomplete matrix appears when some elements are missing. The paper aims to implement Gradient descent method for minimization of Perron eigenvalue problem that arises from incomplete pairwise comparison matrices. Numerical example is given at the end.